The sleeper and the spindle - Gaiman, Neil (London Bloomsbury, 2016)
The Sleeper and the Spindle by Neil Gaiman is a reimagined fairy tale that blends elements of Sleeping Beauty and Snow White in a dark and captivating way. The story follows a queen (reminiscent of Snow White) who, on the eve of her wedding, embarks on a perilous journey to a neighboring kingdom. There, an enchanted sleep has taken hold, spreading from the cursed castle where a mysterious "sleeper" lies, a victim of a spell. Accompanied by three dwarfs, the queen travels through the sleeping land, encountering challenges as she seeks to break the curse. The tale twists the traditional narrative of a helpless princess waiting for rescue, offering a strong, independent heroine who takes action into her own hands. The story explores themes of power, sacrifice, and the subversion of classic fairy tale tropes, all wrapped in Gaiman$1 (Bs signature dark, lyrical prose. Illustrated by Chris Riddell, the book is as visually enchanting as it is narratively rich, with detailed, gothic-style artwork that complements the mood of the story.s